Estimación del error en cierta clase de métodos numéricos combinados de estrategia recorrectora - Marrero, Aymée (2004)
This paper shows an analysis of the order for the approximation and roundoff errors in combined numerical scheme with recorrector strategy of Adams–Moulton–Bashfort family. These methods are used for the numerical solution of the estimation problem in models defined by dynamical ODE. Our interest is avail oneself of “family or kind” of methods which will be efficient or at least competitive for the numericalsolutions of this type of problems. This strategy is consistent with the present tendency in the use of models with minimal square objective function for the adjustment via optimization algorithms with and without constrained and explicit, semi-explicit or implicit numerical methods.